2010
DOI: 10.1111/j.1547-5069.2009.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nursing Unit Turnover on Patient Outcomes in Hospitals

Abstract: Managing nursing unit turnover within appropriate levels at the nursing unit is critical to delivering high-quality patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 28 publications
4
113
0
4
Order By: Relevance
“…As mentioned previously, caring behaviors and relational coordination are related to patient satisfaction in other care settings, [8,16] and thus, the finding of this study is supported by those of the previous studies. In a home care setting, given the short nature of visits, home visiting nurses have less time to directly assess and respond to clients' needs than do nurses working in hospitals or institutional care facilities.…”
Section: Published By Sciedu Presssupporting
confidence: 82%
See 1 more Smart Citation
“…As mentioned previously, caring behaviors and relational coordination are related to patient satisfaction in other care settings, [8,16] and thus, the finding of this study is supported by those of the previous studies. In a home care setting, given the short nature of visits, home visiting nurses have less time to directly assess and respond to clients' needs than do nurses working in hospitals or institutional care facilities.…”
Section: Published By Sciedu Presssupporting
confidence: 82%
“…For example, relational coordination among nursing staff in hospitals has a positive impact on patient satisfaction. [8] Nurses' and nursing aids' relational coordination might enhance the quality of life among nursing home residents. [9] However, the effects of relational coordination have not been identified, especially in home care settings.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the units with moderate levels of turnover were prone to have lower levels of work group learning when compared with those with no turnover (p < 0.01), while nursing units with low levels of turnover were prone to have fewer falls among patients than nursing units with no rotation (p < 0.05). Furthermore, the cohesion of the work group and the relational coordination had a positive impact on patient satisfaction (p < 0.01) and increased learning, leading to fewer occurrences of serious medication errors (p < 0.05) (29) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, turnover leads to higher rate of accidents and absenteeism among remaining nurses [15,16]. Likewise, nursing turnover impacts safe medication practice by increasing errors, decreasing the channels of communication among nurses and between nurses and other healthcare providers which results in poor patient satisfaction [17,18].…”
Section: Introductionmentioning
confidence: 99%